Friends of the Law: Luther's Use of the Law for the Christian Life. By Edward A. Engelbrecht - Methuen, Charlotte (The journal of theological studies, 2014)
In this work, and in sometimes tendentious style, Edward Engelbrecht, senior editor at Concordia Publishing House, argues that Luther consistently maintained the positive use of the Law for justified Christians, and that in doing so he effectively taught the third use of the Law. This book is, as Engelbrecht acknowledges, a survey; it is also intended as a contribution to current debates within American Lutheranism about sexuality, although Engelbrecht does not spell out the implications of his conclusions in this area. Its thesis is, however, potentially of wider interest for Luther scholars.